The Market for non-traditional agricultural exports - Hallam, David, 1953-; Food and Agriculture Organization of the United Nations. Raw Mate rials, Tropical and Horticultural Products Service (Rome : Raw Materials, Tropical and Horticultural Products Service Commodities and Trade Division, Food and Agriculture Organization of t he United Nations, 2004)
An overview of market for non-traditional agricultural exports(NTAEs ). Focuses upon the trends in international trade in these products, t he trade and import policies of the major destination buyers, the exten t of the "adding-up" problem for seledted NTAEs, the lessons learned, a nd the prospects for developing niche markets for organic and fair trad e NTAEs.
Includes bibliographical references (p. 81-82).
Keywords: Produce trade -- statistics